Color Imaging XVI: Displaying, Processing, Hardcopy, and Applications 2011
DOI: 10.1117/12.874359
|View full text |Cite
|
Sign up to set email alerts
|

Preferred skin color enhancement for photographic color reproduction

Abstract: Skin tones are the most important colors among the memory color category. Reproducing skin colors pleasingly is an important factor in photographic color reproduction. Moving skin colors toward their preferred skin color center improves the color preference of skin color reproduction. Several methods to morph skin colors to a smaller preferred skin color region has been reported in the past. In this paper, a new approach is proposed to further improve the result of skin color enhancement. An ellipsoid skin col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…As a consequence, it can be concluded that people across various cultures and nationalities seem to have a quite common and consistent notion of how skin colors should ideally look like. This basically emphasizes the importance of skin colors in the context of preference and memory, which has already been confirmed by various authors 8,57‐64 …”
Section: Color Appearance Rating Results Of Chinese and German Observerssupporting
confidence: 80%
“…As a consequence, it can be concluded that people across various cultures and nationalities seem to have a quite common and consistent notion of how skin colors should ideally look like. This basically emphasizes the importance of skin colors in the context of preference and memory, which has already been confirmed by various authors 8,57‐64 …”
Section: Color Appearance Rating Results Of Chinese and German Observerssupporting
confidence: 80%
“…Cross‐cultural preferences show that Asians prefer less chromatic skin tones than Caucasians and Africans, and Africans prefer more chromatic skin tone for Caucasian and Asian skin tone images than Caucasians and Asians themselves. Interobserver variability was larger for Africans than for Caucasians and Asians 5,6 …”
Section: Introductionmentioning
confidence: 83%
“…Then, using D65 as the reference white point, the images were converted from XYZ to CIELAB color space. From previous research, it is known that skin colors exhibit an ellipsoidal distribution in the CIELAB color space [11]. Moreover, under the D65 illumination condition, the parameters of the ellipsoid corresponding to a specific ethnicity in the CIELAB color space are well-defined [12].…”
Section: Facial Skin Pixel Segmentationmentioning
confidence: 99%
“…As is mentioned above, it's known that for a specific ethnicity, the position and parameters of the skin color ellipsoid in the CIELAB color space is determined [12], and this skin color ellipsoid (50% acceptance ellipsoid in PMCC) [14] can be considered as a standard three-dimensional skin color gamut. Which means when capturing an image containing skin color, regardless of the lighting conditions during the photo capture, as long as the correct reference white point was chosen during the conversion process from XYZ to LAB, the result Lab value of skin color should fall within this standard skin color gamut.…”
Section: Illumination Estimationmentioning
confidence: 99%